Aqueous zinc ion battery electrolyte containing ether-based organic solvent and application of aqueous zinc ion battery electrolyte
By using the combination of electrolytic solution and modified diaphragm with ether -based organic solvents in the water -based zinc battery, the combination of electrolytic septum and ultra -high load iodine positive materials solves the problem of decline in performance decline and safety hazards under extreme conditions under extreme conditions, and achieves realization. The battery capacity and cycle stability are improved.
Patent Information
- Application Number
- CN202411653803.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In practical applications, high-load zinc-iodine batteries face problems such as zinc negative electrode dendrite formation, iodine positive electrode dissolution and loss, performance degradation and safety hazards at extreme temperatures.
The water -based zinc ion electrolyte with ether -based organic solvents is used, and the electrolyte is prepared through the combination of polychloride, de -ion water and ether -based organic solvents, and combined with modified diaphragm and ultra -high load iodine positive materials to build a full -all -round material to build a full -all -round material and ultra -high load iodine. Battery system.
Effectively suppress side reactions, protect the negative electoscularity of zinc, improve the capacity and cycle stability of the battery, and operate efficiently within the wide temperature range, which improves the energy density and stability of the battery.
Smart Images

Figure CN119381593A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aqueous zinc ion battery electrolytes, and in particular to an aqueous zinc ion battery electrolyte containing an ether-based organic solvent and applications thereof. Background Art
[0002] With the continuous development of society, energy demand is showing a growing trend, and the exploration of various energy sources and large-scale energy storage systems is imminent. Economical energy storage systems built with sustainable and rechargeable batteries can more effectively cope with diverse energy storage scenarios. Lithium-ion batteries (LIBs) occupy a leading position in the market in portable electronics and electric vehicles due to their high energy efficiency and high energy density. However, safety issues related to volatility, high manufacturing costs and flammable electrolytes have seriously restricted their sustainable development. Aqueous zinc-ion batteries (AZIBs) can provide higher volumetric energy density and have become a strong candidate to replace lithium-ion batteries. As a potential new energy storage device, high-load zinc-iodine batteries have attracted widespread research interest due to their high energy density, low cost and environmental friendliness.
[0003] In the past few decades, high-load zinc-iodine batteries have faced many challenges in practical applications. Under high-load conditions, zinc anodes are prone to form dendrites, resulting in decreased battery performance and safety hazards. Solving this problem requires optimizing the electrode structure, modifying the battery separator, and using suitable electrolytes. The iodine cathode is prone to dissolution and loss during the charge and discharge process, affecting the cycle life of the battery. Improving the stability of the iodine cathode can be achieved by designing new cathode materials and optimizing the electrode preparation process. The selection of a suitable electrolyte is crucial to improving the performance of high-load zinc-iodine batteries. At the same time, factors such as the ionic conductivity, stability, and compatibility of the electrolyte with the electrode need to be considered. In addition, the application of AZIBs in extreme environments such as high or low temperatures also faces great challenges. Increased temperature will accelerate side reactions at the electrolyte / electrode interface, resulting in the risk of thermal runaway; lowered temperature will aggravate the polarization of AZIBs. As a pure aqueous electrolyte, it is very easy to freeze below zero, thereby limiting ion transfer, internal open circuit, and then leading to battery failure. Summary of the invention
[0004] In order to solve the above technical problems, the purpose of the present invention is to provide an aqueous zinc ion battery electrolyte containing an ether-based organic solvent and its application, which can effectively inhibit side reaction problems, protect the zinc negative electrode, thereby improving the capacity and cycle stability of the battery, and can operate efficiently in a wide temperature range.
[0005] The technical solution of the present invention to solve the above technical problems is as follows: an aqueous zinc ion battery electrolyte containing an ether-based organic solvent is provided, comprising the following components: zinc perchlorate, deionized water and an ether-based organic solvent.
[0006] Furthermore, the concentration of zinc perchlorate in the electrolyte is 0.5-3 mol / L.
[0007] Furthermore, the ether-based organic solvent is diethylene glycol dimethyl ether or ethylene glycol dimethyl ether.
[0008] Furthermore, the volume fraction of the ether-based organic solvent in the electrolyte is 20%-60%.
[0009] Furthermore, the preparation method of the aqueous zinc ion battery electrolyte containing an ether-based organic solvent is: deionized water and an ether-based organic solvent are mixed, and then zinc perchlorate is added and mixed evenly.
[0010] The present invention also provides application of the aqueous zinc ion battery electrolyte containing the ether-based organic solvent in an aqueous zinc ion battery.
[0011] The present invention also provides an aqueous zinc-iodine battery, characterized in that it comprises an aqueous zinc-ion battery electrolyte containing an ether-based organic solvent, a diaphragm and an iodine positive electrode material.
[0012] Furthermore, the diaphragm is a sulfonated polyethersulfone diaphragm, and the preparation method is as follows: polyethersulfone, sulfonated polyethersulfone, polyvinylidene fluoride, polyvinyl pyrrolidone, polyethylene glycol and N,N-dimethylacetamide are mixed in a mass ratio of 1.2-1.4:0.2:0.05:0.25:0.1:8.1, and the mixture is stirred and heated at 60-70°C for 2-4h to dissolve to obtain a spinning solution, which is then loaded into a syringe and electrospun at room temperature. The working voltage and flow rate during spinning are 19 kV and 1.5 mL h, respectively. -1 , the distance between the needle and the collector was 15 cm, and a sulfonated polyethersulfone membrane was obtained.
[0013] Furthermore, the diaphragm is a sulfonated polyetheretherketone diaphragm, and the preparation method is as follows: polyetheretherketone, sulfonated polyetheretherketone, polyvinylidene fluoride, polyvinyl pyrrolidone, polyethylene glycol and N,N-dimethylacetamide are mixed in a mass ratio of 1.2-1.4:0.2:0.05:0.25:0.1:8.1, and the mixture is stirred and heated at 60-70°C for 2-4h to dissolve to obtain a spinning solution, which is then loaded into a syringe and electrospun at room temperature. The working voltage and flow rate during spinning are 19 kV and 1.5 mL h, respectively. -1 , the distance between the needle and the collector was 15 cm, and a sulfonated polyethersulfone membrane was obtained.
[0014] The beneficial effect of adopting a further technical solution is that the sulfonic acid modified membrane has a unique sulfonic acid group, which can produce a strong electrostatic interaction with polyiodide anions, thereby effectively inhibiting the shuttle effect of the interface, which is beneficial to improving the capacity and cycle life of the battery.
[0015] Furthermore, the iodine positive electrode material is an ultra-high loaded iodine positive electrode, and the preparation method is: evenly mix the conductive carbon black and the iodine element in a mass ratio of 20-40:60-80, heat treat at 70-90°C in a vacuum for 1-10h, and then evenly mix with the conductive carbon black and the binder in a mass ratio of 80:10:10, roll it onto a titanium mesh, and dry it at 40°C to obtain an ultra-high loaded iodine positive electrode.
[0016] The beneficial effects of taking further technical solutions are: the ultra-high iodine loading positive electrode has a high specific surface area and good conductivity, which can improve the capacity and cycle stability of the battery, and can operate efficiently in a wide temperature range.
[0017] Furthermore, the conductive carbon black is one of Ketjen black and activated carbon.
[0018] Furthermore, the binder is polytetrafluoroethylene (PTFE).
[0019] The present invention has the following beneficial effects:
[0020] 1. The electrolyte containing an ether-based organic solvent of the present invention adopts conventional medicines, has a simple preparation method, and the solvent itself has a low freezing point, which reduces the freezing point of the electrolyte. When applied to aqueous zinc ion batteries, it shows good reversibility and excellent electrochemical performance, and also broadens its operating temperature range.
[0021] 2. Diethylene glycol dimethyl ether and ethylene glycol dimethyl ether can be broken by Zn 2+ The reversibility and safety of zinc-ion batteries are comprehensively improved by improving the solvation layer structure, combining with water molecules to form a hydrogen bond network, inhibiting corrosion and hydrogen evolution reaction caused by active water decomposition, and achieving excellent electrochemical performance.
[0022] 3. The full battery assembled by the aqueous zinc ion battery electrolyte containing the ether-based organic solvent of the present invention and the high-load carbon-containing iodine positive electrode can store more energy per unit volume or mass, improve the energy density of the battery, and show higher stable cyclability and capacity retention rate, which can meet various application scenarios with high energy requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Cycling performance diagram of Zn / Zn symmetric battery assembled with electrolytes prepared with different volume fractions of diethylene glycol dimethyl ether at 25°C;
[0024] Figure 2Cycling performance diagram of Zn / Zn symmetric battery assembled with electrolytes prepared with different volume fractions of ethylene glycol dimethyl ether at 25°C;
[0025] Figure 3 The cycle performance diagram of the Zn / Zn symmetric battery assembled with the electrolyte prepared with or without diethylene glycol dimethyl ether at 40°C;
[0026] Figure 4 The cycle performance diagram of the Zn / Zn symmetric battery assembled with the electrolyte prepared with or without ethylene glycol dimethyl ether at 40°C;
[0027] Figure 5 The cycle performance diagram of the Zn / Zn symmetric battery assembled with the electrolyte prepared with or without diethylene glycol dimethyl ether at -25°C;
[0028] Figure 6 The cycle performance diagram of the Zn / Zn symmetric battery assembled with the electrolyte prepared with or without ethylene glycol dimethyl ether at -25°C;
[0029] Figure 7 Coulombic efficiency diagram of Zn / Cu half-cell assembled with electrolytes prepared with different volume fractions of diethylene glycol dimethyl ether at 25°C;
[0030] Figure 8 Coulombic efficiency diagram of Zn / Cu half-cell assembled with electrolytes prepared with different volume fractions of ethylene glycol dimethyl ether at 25°C;
[0031] Fig. 9 XRD pattern of the negative electrode zinc sheet of the Zn / Zn symmetric battery assembled with an electrolyte containing 40% ether-based organic solvent after 50 cycles;
[0032] Fig.10 SEM image of the negative electrode zinc sheet of the Zn / Zn symmetric battery assembled with an electrolyte containing 40% ether-based organic solvent after 50 cycles;
[0033] Fig.11 The SEM images of sulfonated polyethersulfone membrane and sulfonated polyetheretherketone membrane;
[0034] Fig.12 This is the long cycle diagram of the Zn / / I2 full battery assembled with the electrolyte containing diethylene glycol dimethyl ether and the sulfonated polyethersulfone separator at 25°C;
[0035] Fig.13 This is the long cycle diagram of the Zn / / I2 full battery assembled with ethylene glycol dimethyl ether electrolyte and sulfonated polyetheretherketone separator at 25°C;
[0036] Fig.14This is the long cycle diagram of the Zn / / I2 full battery assembled with the electrolyte containing diethylene glycol dimethyl ether and the sulfonated polyethersulfone separator at -25°C;
[0037] Fig.15 This is the long cycle diagram of the Zn / / I2 full battery assembled with an electrolyte containing ethylene glycol dimethyl ether and a sulfonated polyetheretherketone separator at -25°C. DETAILED DESCRIPTION
[0038] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific conditions are specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0039] Example 1
[0040] An aqueous zinc ion battery electrolyte containing an ether-based organic solvent comprises the following components: zinc perchlorate, deionized water and an ether-based organic solvent;
[0041] The concentration of zinc perchlorate in the electrolyte is 1.5 mol / L; the ether-based organic solvent is diethylene glycol dimethyl ether, and its volume fraction in the electrolyte is 40%.
[0042] Example 2
[0043] An aqueous zinc ion battery electrolyte containing an ether-based organic solvent comprises the following components: zinc perchlorate, deionized water and an ether-based organic solvent;
[0044] The concentration of zinc perchlorate in the electrolyte is 0.5 mol / L; the ether-based organic solvent is diethylene glycol dimethyl ether, and its volume fraction in the electrolyte is 20%.
[0045] Example 3
[0046] An aqueous zinc ion battery electrolyte containing an ether-based organic solvent comprises the following components: zinc perchlorate, deionized water and an ether-based organic solvent;
[0047] The concentration of zinc perchlorate in the electrolyte is 3 mol / L; the ether-based organic solvent is ethylene glycol dimethyl ether, and its volume fraction in the electrolyte is 60%.
[0048] Example 4
[0049] An aqueous zinc-iodine battery comprises an aqueous zinc-ion battery electrolyte containing an ether-based organic solvent, a diaphragm and an iodine positive electrode material.
[0050] Test Example 1
[0051] Diethylene glycol dimethyl ether and ethylene glycol dimethyl ether were used as ether-based organic solvents, respectively, and mixed with deionized water to prepare solvents with volume fractions of 0%, 20%, 40%, and 60%. Then, zinc perchlorate hexahydrate was added at 1.5 mol / L and stirred and mixed. After ultrasonication, the electrolyte was filtered to obtain an electrolyte. Each electrolyte was then used to assemble a Zn / Zn symmetric cell and a Zn / Cu half-cell. At a current density of 1 mA cm -2 and an area capacity of 0.5 mAh cm -2 The cycle number of the symmetrical battery and the coulombic efficiency of the half cell were tested under the following conditions.
[0052] (1) The cycling performance of Zn / Zn symmetric batteries assembled with electrolytes prepared with different volume fractions of diethylene glycol dimethyl ether at 25°C is shown in the figure. Figure 1 As shown in the figure, it can be clearly seen that the battery assembled by the electrolyte without adding diethylene glycol dimethyl ether short-circuited after 63 hours of circulation, while after adding 40% diethylene glycol dimethyl ether, the Zn / Zn symmetric battery can stably cycle for more than 3000 hours. It can be seen that diethylene glycol dimethyl ether has a positive effect on the stable deposition of zinc ions.
[0053] (2) The cycling performance of Zn / Zn symmetric batteries assembled with electrolytes prepared with different volume fractions of ethylene glycol dimethyl ether at 25°C is shown in the figure. Figure 2 As shown in the figure, it can be clearly seen that the battery assembled by the electrolyte without adding ethylene glycol dimethyl ether short-circuited after 50 hours of circulation, while after adding 40% ethylene glycol dimethyl ether, the Zn / Zn symmetric battery can stably cycle for more than 880 hours. It can be seen that ethylene glycol dimethyl ether has a positive effect on the stable deposition of zinc ions.
[0054] (3) Whether the electrolyte prepared with diethylene glycol dimethyl ether contains Zn / Zn symmetric battery assembled at 40°C is as follows Figure 3 As shown in the figure, it can be clearly seen that the battery assembled by the electrolyte without diethylene glycol dimethyl ether short-circuited after 55 hours of cycling, while after adding 40% diethylene glycol dimethyl ether, the Zn / Zn symmetric battery can stably cycle for more than 600 hours. It can be seen that diethylene glycol dimethyl ether has a positive effect on the stable deposition of zinc ions.
[0055] (4) The cycling performance of a Zn / Zn symmetrical battery assembled with an electrolyte prepared with ethylene glycol dimethyl ether at 40°C is shown in the figure below. Figure 4 As shown in the figure, it can be clearly seen that the battery assembled by the electrolyte without ethylene glycol dimethyl ether short-circuited after 44 hours of circulation, while after adding 40% ethylene glycol dimethyl ether, the Zn / Zn symmetric battery can stably cycle for more than 430 hours. It can be seen that ethylene glycol dimethyl ether has a positive effect on the stable deposition of zinc ions.
[0056] (5) Is the cycling performance of a Zn / Zn symmetrical battery assembled with an electrolyte prepared with diethylene glycol dimethyl ether at -25°C as shown in the figure below? Figure 5 As shown in the figure, it can be clearly seen that the battery assembled by the electrolyte without diethylene glycol dimethyl ether short-circuited after 255 hours of cycling, while after adding 40% diethylene glycol dimethyl ether, the Zn / Zn symmetric battery can stably cycle for more than 2500 hours. It can be seen that diethylene glycol dimethyl ether has a positive effect on the stable deposition of zinc ions.
[0057] (6) Is the cycling performance of a Zn / Zn symmetrical battery assembled with an electrolyte prepared with ethylene glycol dimethyl ether at -25°C as shown in the figure below? Figure 6 As shown in the figure, it can be clearly seen that the battery assembled by the electrolyte without ethylene glycol dimethyl ether short-circuited after 221 hours of circulation, while after adding 40% ethylene glycol dimethyl ether, the Zn / Zn symmetric battery can be stably cycled for more than 1500 hours. It can be seen that ethylene glycol dimethyl ether has a positive effect on the stable deposition of zinc ions.
[0058] (7) The coulombic efficiency of Zn / Cu half-cells assembled with electrolytes prepared with different volume fractions of diethylene glycol dimethyl ether at 25°C is shown in the figure below. Figure 7 As shown in the figure, it can be clearly seen that the battery assembled by the electrolyte without adding diethylene glycol dimethyl ether short-circuited after 25 hours of circulation, while after adding 40% diethylene glycol dimethyl ether, the Zn / Cu half-cell can stably cycle for more than 2100 hours and the coulombic efficiency is maintained at 97.51%. It can be seen that diethylene glycol dimethyl ether can make zinc ions stably deposited on the surface of the Cu substrate.
[0059] (8) The coulombic efficiency of Zn / Cu half-cells assembled with electrolytes prepared with different volume fractions of ethylene glycol dimethyl ether at 25°C is shown in the figure below. Figure 8 As shown in the figure, it can be clearly seen that the battery assembled by the electrolyte without adding diethylene glycol dimethyl ether short-circuited after 18 hours of cycling, while after adding 40% diethylene glycol dimethyl ether, the Zn / Cu half-cell can stably cycle for more than 1400 hours and the coulombic efficiency is maintained at 98.56%. It can be seen that diethylene glycol dimethyl ether can make zinc ions stably deposited on the surface of the Cu substrate.
[0060] (9) The XRD image of the negative electrode zinc sheet of the Zn / Zn symmetric battery assembled with an electrolyte containing 40% ether-based organic solvent after 50 cycles is shown in Figure 2. Fig. 9 As shown in the figure, it can be clearly seen that the peak of the by-product Zn5(OH)8Cl2H2O can be clearly found in the battery assembled by the electrolyte without adding ether-based organic solvents. After adding 40% of diethylene glycol dimethyl ether or ethylene glycol dimethyl ether, the peak intensity of the by-product is significantly weakened, proving that ether-based organic solvents can effectively inhibit the formation of by-products.
[0061] The negative electrode zinc sheet was observed by scanning electron microscopy (SEM). Fig.10 As shown in the figure, it can be clearly seen that in the battery assembled by the electrolyte without adding ether-based organic solvents, a layer of polygonal by-products can be clearly found on the surface of the zinc sheet, while after adding 40% of diethylene glycol dimethyl ether or ethylene glycol dimethyl ether, the surface coating of the zinc sheet is uniform and no by-products are generated, proving that ether-based organic solvents can uniformly guide zinc deposition.
[0062] Test Example 2
[0063] Polyethersulfone, sulfonated polyethersulfone, polyvinylidene fluoride, polyvinyl pyrrolidone, polyethylene glycol and N,N-dimethylacetamide were mixed in a mass ratio of 1.3:0.2:0.05:0.25:0.1:8.1, stirred and heated at 65 °C for 3 h to dissolve to obtain a spinning solution, which was then loaded into a syringe and electrospun at room temperature. The working voltage and flow rate during spinning were 19 kV and 1.5 mL / h, respectively. -1 , the distance between the needle and the collector is 15 cm, and a sulfonated polyethersulfone membrane is obtained; polyethersulfone and sulfonated polyethersulfone are replaced by polyetheretherketone and sulfonated polyetheretherketone, respectively, and a sulfonated polyetheretherketone membrane is obtained by the same method; the SEM images of the sulfonated polyethersulfone membrane and the sulfonated polyetheretherketone membrane are shown in Fig.11 As shown, it can be clearly seen that the diaphragm is composed of extremely fine fibers interwoven together, and the fibers are dense and thin.
[0064] Ketjen black and iodine element were uniformly mixed in a mass ratio of 30:70, heat treated at 80°C in vacuum for 3 hours, then uniformly mixed with Ketjen black and polytetrafluoroethylene binder in a mass ratio of 80:10:10, rolled onto a titanium mesh, and dried at 40°C to form a working electrode, thereby obtaining an iodine positive electrode material.
[0065] A Zn / / I2 full battery was assembled using an electrolyte containing 40% diethylene glycol dimethyl ether or ethylene glycol dimethyl ether, a separator and an iodine positive electrode material, and the charge and discharge curves as well as the long cycle stability were measured at a current density of 2C.
[0066] (1) The long cycle diagram of the Zn / / I2 full battery assembled with diethylene glycol dimethyl ether electrolyte and sulfonated polyethersulfone separator at 25°C is shown in Fig.12 As shown, it can be clearly seen that the full battery containing diethylene glycol dimethyl ether and sulfonated polyethersulfone membrane has a higher charge and discharge capacity and the capacity does not decay after 5000 cycles.
[0067] (2) The long cycle diagram of the Zn / / I2 full battery assembled with ethylene glycol dimethyl ether electrolyte and sulfonated polyetheretherketone separator at 25°C is shown in Fig.13As shown, it can be clearly seen that the full battery containing ethylene glycol dimethyl ether and sulfonated polyetheretherketone separator has a higher charge and discharge capacity and the capacity does not decay after 4000 cycles.
[0068] (3) The long cycle diagram of the Zn / / I2 full battery assembled with diethylene glycol dimethyl ether electrolyte and sulfonated polyethersulfone separator at -25°C is shown in Fig.14 As shown, it can be clearly seen that the full battery containing diethylene glycol dimethyl ether and sulfonated polyethersulfone membrane has a higher charge and discharge capacity and the capacity does not decay after 1000 cycles.
[0069] (4) The cycle diagram of the Zn / / I2 full cell assembled with ethylene glycol dimethyl ether electrolyte and sulfonated polyetheretherketone separator at -25°C is shown in Figure 2. Fig.15 As shown, it can be clearly seen that the full battery containing ethylene glycol dimethyl ether and sulfonated polyethersulfone membrane has a higher charge and discharge capacity and the capacity does not decay after 1000 cycles.
[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An aqueous zinc ion battery electrolyte containing an ether-based organic solvent, characterized in that: The invention comprises the following components: zinc perchlorate, deionized water and an ether-based organic solvent.
2. The aqueous zinc ion battery electrolyte containing an ether-based organic solvent according to claim 1, characterized in that The concentration of zinc perchlorate in the electrolyte is 0.5-3 mol / L.
3. The aqueous zinc ion battery electrolyte containing an ether-based organic solvent according to claim 1, characterized in that The ether-based organic solvent is diethylene glycol dimethyl ether or ethylene glycol dimethyl ether.
4. The aqueous zinc ion battery electrolyte containing an ether-based organic solvent according to claim 1, characterized in that The volume fraction of the ether-based organic solvent in the electrolyte is 20%-60%.
5. The aqueous zinc ion battery electrolyte containing an ether-based organic solvent according to claim 1, characterized in that: The preparation method comprises the following steps: mixing deionized water and the ether-based organic solvent, adding zinc perchlorate and mixing the mixture evenly.
6. Use of the aqueous zinc ion battery electrolyte containing an ether-based organic solvent according to any one of claims 1 to 5 in an aqueous zinc ion battery.
7. An aqueous zinc-iodine battery, characterized in that: The invention comprises the aqueous zinc ion battery electrolyte containing an ether-based organic solvent as claimed in claim 1, a diaphragm and an iodine positive electrode material.
8. The aqueous zinc-iodine battery according to claim 7, characterized in that: The diaphragm is a sulfonated polyethersulfone diaphragm. The preparation method of the sulfonated polyethersulfone diaphragm is as follows: polyethersulfone, sulfonated polyethersulfone, polyvinylidene fluoride, polyvinyl pyrrolidone, polyethylene glycol and N,N-dimethylacetamide are mixed in a mass ratio of 1.2-1.4:0.2:0.05:0.25:0.1:8.1, and the mixture is stirred and heated at 60-70°C for 2-4h to dissolve to obtain a spinning solution, which is then loaded into a syringe and electrostatically spun at room temperature. The working voltage and flow rate during spinning are 19 kV and 1.5 mL h, respectively. -1 , the distance between the needle and the collector was 15 cm, and a sulfonated polyethersulfone membrane was obtained.
9. The aqueous zinc-iodine battery according to claim 7, characterized in that: The diaphragm is a sulfonated polyetheretherketone diaphragm. The preparation method of the sulfonated polyetheretherketone diaphragm is as follows: polyetheretherketone, sulfonated polyetheretherketone, polyvinylidene fluoride, polyvinyl pyrrolidone, polyethylene glycol and N,N-dimethylacetamide are mixed in a mass ratio of 1.2-1.4:0.2:0.05:0.25:0.1:8.1, and the mixture is stirred and heated at 60-70°C for 2-4h to dissolve to obtain a spinning solution, which is then loaded into a syringe and electrostatically spun at room temperature. The working voltage and flow rate during spinning are 19 kV and 1.5 mL h, respectively. -1 , the distance between the needle and the collector was 15 cm, and a sulfonated polyethersulfone membrane was obtained.
10. The aqueous zinc-iodine battery according to claim 7, characterized in that: The iodine positive electrode material is an ultra-high-load iodine positive electrode. The preparation method of the ultra-high-load iodine positive electrode is: conductive carbon black and iodine element are evenly mixed in a mass ratio of 20-40:60-80, heat-treated at 70-90° C. in a vacuum for 1-10 hours, and then evenly mixed with conductive carbon black and a binder in a mass ratio of 80:10:10, rolled onto a titanium mesh, and dried at 40° C. to obtain an ultra-high-load iodine positive electrode.